2016
DOI: 10.4172/2376-0427.1000242
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Vitiligo by Needling with Topical 5 Fluorouracil

Abstract: Introduction: Vitiligo is a chronic acquired disorder presenting with depigmented macules and patches. The response to treatment is variable as no single therapy produces predictably good results. Needling with topical 5% 5 fluorouracil in vitiligo has been found to be promising, effective and safe modality of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Vedamurthy et al conducted a trial on 3 cases of vitiligo using needling and 5‐FU, and the cases showed >75% repigmentation, but we cannot compare with his study as it included only 3 cases.…”
Section: Discussionmentioning
confidence: 91%
“…Vedamurthy et al conducted a trial on 3 cases of vitiligo using needling and 5‐FU, and the cases showed >75% repigmentation, but we cannot compare with his study as it included only 3 cases.…”
Section: Discussionmentioning
confidence: 91%
“…The efficacy of dermabrasion combined with topical 5‐FU cream reached 56.67% in 4 months and 73.33% in 6‐month follow‐up . In a case report, 75% improvement was reported in three patients after multiple superficial punctures of vitiligo patches combined application of 5‐FU cream . The efficacy of topical 5‐FU combined with micro‐needling was superior to micro‐needling alone in 6 months after therapy (60.34% vs 22.22%, respectively) and another report of more than 75% repigmentation in 49% of the vitiligo patches after topical 5‐FU combined with micro‐needling .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast our studied group A, showed good to excellent response in 66.7% of cases and 33.3% poor response only 3 cases [10%] showed no response. Also, Vedamurthy et al [10] reported on three patients of resistant vitiligo. They were subjected to needling with topical 5% 5-fluorouracil application every two weeks for three months, along with their ongoing therapy.…”
Section: Discussionmentioning
confidence: 99%